The productivity and bioenergetic efficiency of the new variety of sainfoin ‘Shuravi’ - S. A. Ignatiev; T. V. Gryazeva; N. G. Ignatieva; G. V. Metlina (Зерновое хозяйство России, 2018)
The article presents the results of three cycles of study of productivity and quality of sainfoin variety ‘Shuravi’. The purpose of the study is to establish the advantages of economic-biological characteristics of sainfoin ‘Shuravi’ over the standard variety ‘Zernogradsky 2’. The experiments were conducted by Agricultural Research Center “Donskoy” in 2012-2016. The soil of the experimental fields is heavy loamy, carbonaceous black earth (chernozem) with a deep layer of humus (120 cm) and high content of carbon. The reaction of soil solution is nearly neutral (pH 7.0-7.1). The content of easily hydrolyzable nitrogen is of 60-110 mg/kg of soil; the content of movable phosphorus is 18.5 mg/kg of soil; the content of changeable potassium is of 342 mg/kg of soil. On average the productivity of sainfoin green mass during three cycles was 31.9 t/ha that is on 3.2 t/ha or 11.1% more than that of the standard variety. The productivity of dry matter of the variety ‘Shuravi’ was 8.06 t/ha on average during the studied period, that was on 1.16t/ha or 16.8% more than that of the variety ‘Zernogradsky 2’. The sainfoin variety ‘Shuravi’ showed a better productivity of kernels than the standard variety during all years of study. The grain productivity of ‘Shuravi’ was 0.84t/ha, that is on 0.22t/ha or 35.5% more than that of the variety ‘Zernogradsky 2’. The variety ‘Shuravi’ surpasses the standard variety in such traits as early maturity, fast and strong germination, tillering and leaf formation. The yield of forage units of the variety ‘Shuravi’ is on 11.2% more than that of the variety ‘Zernogradsky 2’. The amount of digestible protein in ‘Shuravi’ is on 12.5% more than that of ‘Zernogradsky 2’. The yield energy of ‘Shuravi’ was on 15.9% more than that of ‘Zernogradsky 2’ at a higher coefficient of energetic efficiency and a smaller index of energy capacity of product.